2021
DOI: 10.1111/ajag.12941
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patterns of personal alarm system use and impacts on outcomes

Abstract: Objectives: To describe the patterns of personal emergency response systems (PERS) use in a statewide cohort of older Australians. Methods: PERS data from clients enrolled in the Personal Alarm Victoria program between January 2014 and June 2017 were analysed. Alarm activation reasons were extracted, and a medical record audit was performed for a sub-cohort of patients admitted to a local hospital following an alarm event. Descriptive statistics were used. Results: There were 42,180 clients enrolled during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 20 publications
0
19
1
Order By: Relevance
“…For example, extended periods of time spent lying on the ground after falls often lead to poor outcomes, including serious injuries and emergency department visits (Bloch et al, 2017; De San Miguel et al, 2015; Johnston et al, 2010). Although PERS were originally designed to assist people after falls, because of the ease of use—they are designed with the needs of people with fewer technology skills in mind—their use has since expanded to other physical and mental emergencies (Agboola et al, 2017; Andrew et al, 2021; Chang et al, 2020; McLean, 2016; Young et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, extended periods of time spent lying on the ground after falls often lead to poor outcomes, including serious injuries and emergency department visits (Bloch et al, 2017; De San Miguel et al, 2015; Johnston et al, 2010). Although PERS were originally designed to assist people after falls, because of the ease of use—they are designed with the needs of people with fewer technology skills in mind—their use has since expanded to other physical and mental emergencies (Agboola et al, 2017; Andrew et al, 2021; Chang et al, 2020; McLean, 2016; Young et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Alert systems may also give users and their loved ones a sense of security, improving functional independence and reducing fear of falling. 4 Personal emergency response systems (PERS) such as that described by Andrew et al 5 are frequently prescribed by health professionals and funded in Australia by a variety of agencies (eg private health insurance schemes, Department of Veterans Affairs, Commonwealth Home Care Program, Transition Care and the National Disability Insurance Scheme for under 65s).…”
mentioning
confidence: 99%
“…Their results also reinforce the numerous comorbidities presented in the older population (mean age of 80) particularly respiratory conditions. When considering a subcohort of the sample that was admitted to a local hospital, Andrew et al 5 identified common medical INVITED COMMENTARY conditions such as cardiovascular or respiratory disease as a primary diagnosis and a high percentage (78%) readmissions at 12 months.…”
mentioning
confidence: 99%
See 2 more Smart Citations